Christianity and Cultures : Shaping Christian Thinking in Context - Farr, Bernard C.; Singh, David Emmanuel (Book collections on Project MUSE., 2008)
This volume marks an important milestone, the 25th anniversary of the Oxford Centre for Mission Studies (OCMS). The papers here have been exclusively sourced from Transformation, a quarterly journal of OCMS, and seek to provide a tripartite view of Christianity's engagement with cultures by focusing on the question: how is Christian thinking being formed or reformed through its interaction with the varied contexts it encounters? The subject matters include different strands of theological-missiological thinking, socio-political engagements and forms of family relationships in interaction with.